Misja kanoniczna dla doradców życia rodzinnego - Wybult, Witold (Ius Matrimoniale, 2020)
Code of Canon Law promulgated by John Paul II gave the secular in church the possibility to take part in the service of managing, teaching and sanctifying. Canon 228 seems to be the most significant and fundamental code rule to apply the canonical mission. The first point informs: „Persons who are found suitable are qualified to be admitted by the sacred pastors to those ecclesiastical offices and functions which they are able to exercise according to the precepts of the law”. The following paragraph states: „Persons who excel in necessary knowledge, prudence, and integrity are qualified to assist the pastors of the Church as experts and advisors, even in councils according to the norm of law”. Code of Canon Law of 1983, which in a very synthetic way formalises the preparation for marriage, draws the attention to some significant pastoral elements and, which is important, leaves the initiative in all not specified matters to specific conferences of Bishops and ordinaries of place. Polish Episcopal Conference meeting the expectations of the teaching of the Second Ecumenical Council of the Vatican and code norms published „Family Pastoral Directory”, which became the legal foundation for the requirement of demanding the sanction of competent power for family life counsellors to serve in Church, which formally means having missio canonica. Polish dioceses respectively are developing the norms relative to the requirements set for family life counsellors during diocese synods or outside of them.